Immunosuppressant and neuromyelitis optica spectrum disorder: optimal treatment duration and risk of discontinuation. (11th June 2022) - Li, Rui; Li, Cong; Huang, Qiao; Liu, Zifeng; Chen, Jingjing; Zhang, Bingjun; Liu, Chunxin; Shu, Yaqing; Wang, Yuge; Kermode, Allan G.; Qiu, Wei
Abstract: Background and purpose: Preventing relapse by immunosuppressants (ISs) is critical for the prognosis of neuromyelitis optica spectrum disorder (NMOSD); however, the optimal duration of IS treatment is still under discussion. The objective was to explore the optimal duration of IS treatment and the risk of IS discontinuation for NMOSD. Method: This cohort study was conducted at a major neurological center that housed the largest NMOSD database in South China. Eligible participants were patients with NMOSD undergoing IS treatment. The main outcome measures were changes in relapse risk based on IS treatment duration, clinical outcomes and predictors of relapse following IS discontinuation. Results: In total, 343 patients were included in this study. The duration of IS treatment was strongly associated with a decrease in relapse risk (hazard ratio [HR] 0.53, p < 0.001). Continuous IS treatment resulted in decreased relapse HRs within 5 years of receiving IS medication, with a mild rebound starting at 5 years. Rituximab reduced the risk of NMOSD relapse to approximately zero within 3 years. The rate of relapse after IS withdrawal was high (77.5%). As opposed to other ISs, a delayed relapse following rituximab withdrawal was observed in this study. Longitudinal extensive transverse myelitis (HR = 2.023, p = 0.006) was associated with a higher risk of relapse after IS discontinuation. Conclusions: Long‐term IS medication for NMOSD is generally suitable. Patients with longitudinal extensive transverse myelitis had a higher risk of relapse after IS discontinuation. Future studies should explore individualized strategies of rituximab maintenance treatment. Abstract : Continuous azathioprine/mycophenolate mofetil treatment showed a decreased trend in hazard ratio relapse within 5 years of administering medication and a mild rebound starting at the 5‐year time point, similar to that of the overall population, whilst rituximab could reduce the risk of neuromyelitis optica spectrum disorder relapse to approximately zero within 3 years.